Enzymatic process as a potential treatment technology to remove anticancer drugs from wastewater: laccase-assisted degradation of etoposide - Pereira, Camila Senna (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2020.